The COL5A3 and MMP9 genes interact in eczema susceptibility. Issue 3 (19th December 2017) - Margaritte‐Jeannin, P.; Babron, M.‐C.; Laprise, C.; Lavielle, N.; Sarnowski, C.; Brossard, M.; Moffatt, M.; Gagné‐Ouellet, V.; Etcheto, A.; Lathrop, M.; Just, J.; Cookson, W. O.; et al.
Summary: Background: Genetic studies of eczema have identified many genes, which explain only 14% of the heritability. Missing heritability may be partly due to ignored gene–gene (G‐G) interactions. Objective: Our aim was to detect new interacting genes involved in eczema. Methods: The search for G‐G interaction in eczema was conducted using a two‐step approach, which included as a first step, a biological selection of genes, which are involved either in the skin or epidermis development or in the collagen metabolism, and as a second step, an interaction analysis of the selected genes. Analyses were carried out at both SNP and gene levels in three asthma‐ascertained family samples: the discovery dataset of 388 EGEA (Epidemiological study on the Genetics and Environment of Asthma) families and the two replication datasets of 253 SLSJ (Saguenay–Lac‐Saint‐Jean) families and 207 MRCA (Medical Research Council) families. Results: One pair of SNPs, rs2287807 in COL5A3 and rs17576 in MMP9, that were detected in EGEA at P ≤ 10 −5 showed significant interaction by meta‐analysis of EGEA, SLSJ and MRCA samples ( P = 1.1 × 10 −8 under the significant threshold of 10 −7 ). Gene‐based analysis confirmed strong interaction between COL5A3 and MMP9 ( P = 4 × 10 −8 under the significant threshold of 4 × 10 −6 ) by meta‐analysis of the three datasets. When stratifying the data on asthma, this interaction remained in both groups of asthmatic and non‐asthmatic subjects. Conclusion: This study identified significant interaction between two new genes, COL5A3 and MMP9, which may be accounted for by a degradation of COL5A3 by MMP9 influencing eczema susceptibility. Further confirmation of this interaction as well as functional studies is needed to better understand the role of these genes in eczema.